Alteration of Energy Substrates and ROS Production in Diabetic Cardiomyopathy - O. Lorenzo; E. Ramírez; B. Picatoste; J. Egido; J. Tuñón (Mediators of Inflammation)
Diabetic cardiomyopathy is initiated by alterations in energy substrates. Despite excess of plasma glucose and lipids, the diabetic heart almost exclusively depends on fatty acid degradation. Glycolytic enzymes and transporters are impaired by fatty acid metabolism, leading to accumulation of glucose derivatives. However, fatty acid oxidation yields lower ATP production per mole of oxygen than glucose, causing mitochondrial uncoupling and decreased energy efficiency. In addition, the oxidation of fatty acids can saturate and cause their deposition in the cytosol, where they deviate to induce toxic metabolites or gene expression by nuclear-receptor interaction. Hyperglycemia, the fatty acid oxidation pathway, and the cytosolic storage of fatty acid and glucose/fatty acid derivatives are major inducers of reactive oxygen species. However, the presence of these species can be essential for physiological responses in the diabetic myocardium.